Cytotoxin-associated gene antigen-positive strains of Helicobacter pylori and recurring acute coronary syndromes. Issue 6 (1st September 2017) - Niccoli, Giampaolo; Roberto, Marco; D'Amario, Domenico; Scalone, Giancarla; Fracassi, Francesco; Cosentino, Nicola; Candelli, Marcello; Franceschi, Francesco; Crea, Filippo
Abstract: Background: Cytotoxin-associated gene antigen (CagA)-positive strains of Helicobacter pylori have previously been associated with acute coronary syndromes. However, the role of CagA-positive strains of Helicobacter pylori in recurring cardiac events after ST-segment elevation myocardial infarction (STEMI) has not yet been assessed. Methods: We enrolled 181 consecutive patients (155 men, mean age 64±13 years) presenting with STEMI. In all patients, serum levels of IgG anti-CagA were assessed. Levels of IgG anti-hepatitis A virus were also evaluated in all patients in order to exclude the presence of a bystander activation of the immune system. Finally, a previous history of acute coronary syndrome and the rate of major adverse cardiovascular events as a composite of cardiovascular death, recurring myocardial infarction and target lesion revascularisation within 2 years follow-up were evaluated. Results: Anti-CagA IgG seropositive patients presented more frequently with a previous history of acute coronary syndrome compared with seronegative patients (28.3% vs. 14%, P =0.019). Interestingly, no differences were observed between anti-CagA IgG seropositive and anti-CagA IgG seronegative patients concerning the prevalence of anti-hepatitis A virus IgG seropositivity (20% vs. 21.4%, P =0.48). At 2-year follow-up, 40 patients experienced major adverse cardiovascular events. The major adverse cardiovascular event rate was higher in anti-CagA IgG seropositive compared with seronegative patients (hazard ratio 2.25, 95% confidence interval 1.34–2.95, P =0.013), which was confirmed at Cox multivariate analysis (hazard ratio 2.33, 95% confidence interval 1.30–3.14, P =0.009). Conclusions: CagA-positive strains of Helicobacter pylori seem to be involved in the pathogenesis of recurring acute coronary syndromes, and seropositivity for anti-CagA IgG predicts prognosis after STEMI, possibly due to the increased risk of recurring cardiac events.